VALIDATION OF AN ULTRA-HIGH RESOLUTION LIQUID CHROMATOGRAPHY (UHPLC/MS/MS) METHOD FOR THE QUANTIFICATION OF CARBAMATES IN AGRICULTURAL SOIL - Cosco Salguero, Gloria (2022)
This research work proposes the validation of a method by ultra-high pressure liquid chromatography coupled to a triple quadrupole mass spectrometer (UHPLC/MS/MS) with the aim of quantifying carbamates: aldicarb, carbofuran and their metabolites (aldicarb sulfone, aldicarb sulfoxide and carbofuran-3-hydroxy) in different samples of agricultural soils as a starting point for environmental contamination. This method guarantees a good chromatographic separation of the analytes in the samples, the ionization of the molecules and the separation of their fragments, which will be identified by their mass charge ratio(m/z) and their ion ratio, parameters that help to identify to the analytes of interest and calculated at much lower concentrations compared to other pesticide determination methods. The proposed method presents a recovery in the fortified samples with a maximum level of 103,91%, and the precision with the Barlett test with a p-value = 0,327, in addition to other performance parameters according to the technique, the detection limits at 1ug/L and quantification at the 5ug/L level, which shows that the method is more sensitive than the HPLC methods, which were evaluated with statistical software. The evaluation of the validation parameters concluded that the method is accurate and true at 95% confidence, compared to other analysis methods, it improves the analysis time to 15 minutes, and the analytes can be better identified, decreasing the matrix effect.